The Cooperative Pattern of Territorial Development in Hungary: The Expansion, Organisation, and Turnover of the Hangya Cooperative (1898–1923) - Koloh, Gábor (Historical Studies on Central Europe, 2024)
This paper addresses the following question: What is the spatial pattern of the spread of the most significant consumer cooperatives in Hungary in the first quarter of a century following their establishment in 1898? Spatial pattern is employed as an indicator in order to ascertain the spatial developmental differences. My hypothesis is that organising and operating a cooperative is an indicator of community activity with the objective of attaining a superior quality of life. Although the Hangya Consumption Cooperative in Hungary received considerable support from landlords and later the state, the study indicates that local cultural patterns of organisation and the strength of traditional economic districts are significant. Concurrently, the analysis demonstrates that it is possible to delineate the role of social welfare in the establishment and functioning of local consumer organisations. On the other hand, the Hangya’s operations served to disseminate anti-Semitic ideologies. The macro-regional analysis aims to contribute to the broader investigation of peasant farm development, grassroots modernisation, and the discourse on territorial inequality.